Pengukuran kesan kemasukan bilangan pelancong terhadap jumlah kesan ekonomi (TEI) di Pulau Payar menggunakan kaedah System Dynamics - Noraini, Ismail (2016)
Islands in Malaysia have been seen as invaluable resources for the country since the development of tourism based island activities have contributed a lot to the economic growth. The record of tourists’ entries, attests that an increase in tourists’ entry has spurred the economic growth. In addition, the differences of the natural characteristic among these islands can contribute to the Total Economic Impact (TEI). On the other hand, it is also found that the increase of tourists’ entry has given negative impact to the ecosystems such as the coral reefs. Therefore, one method is needed to measure to what extend the coral reef is damaged with the increase of tourists’ entry in an effort to increase the Total Economic Impact (TEI). This study is conducted to develop a simulation model to estimate the Total Economic Impact (TEI) for ecotourism activities in Pulau Payar, the first marine park in Malaysia. Using System Dynamics (SD) methodology, Total Economic Impact (TEI) at Pulau Payar can be determined by looking at the cause and effect relationship between the sub-sectors based on the concept of Total Economic Value (TEV). Sensitivity Analysis and Extreme Cases Analysis methods are employed to validate the findings. This study suggests that Pulau Payar needs to focus on ways and means to increase the entry number of tourists and at the same time to increase the level of awareness about the destruction of coral reefs so that the damage can be reduced. As a result, Total Economic Impact (TEI) can be increased.